Developing an Animal Law Case Book: Knowledge Transfer and Service Learning from Student-Generated Materials - Sophie Riley (Legal Education Review)
This article responds to Justice Leeming’s call for the pedagogy of constitutional law to undergo a rethink. Particularly, how to keep the teaching of constitutional law ‘living, useful and relevant’ and whether constitutional law instruction needs to prioritise new developments in the field over tried and true topics in which the issues are established and less contentious. In discussing the breadth, depth and form of the teaching of the discipline of constitutional law, the article emphasises the need to focus on the method as well as the content of courses and the importance of teaching just enough so that students develop a hunger to learn more themselves. It concludes that many uncertainties about what and how to teach constitutional law come back to Justice Leeming’s invitation to address what we even mean by ‘constitutional law’ in the first place. Answering this question then allows for the shaping of a curriculum that can inspire students while also equipping them with the tools to tackle the constitutional law challenges which lie ahead.